What absolute beginners learn from input. Issue 2 (9th October 2018) - Carroll, Susanne E.; George, Angela
Abstract : Absolute beginners rapidly solve several word learning problems after minimal exposure to second language speech. In this article, we report on laboratory research that supports this claim. Explaining second language acquisition is a goal of foundational research. While our findings are consistent with the generativist enterprise, generativists have been content to describe what learners have acquired while avoiding discussion of the 'how'. We describe a specific generativist approach (the Autonomous Induction Theory) that directly addresses the role of specific learning mechanisms proposed by cognitive psychology. In contrast to alternative non-generative approaches, the Autonomous Induction Theory offers a constrained theory of language acquisition. Both the data from laboratory settings and the theoretical explanations of how adult learners learn have potential implications for language teaching. One should not, however, make teaching recommendations directly from laboratory results. Rather, the findings should be reinterpreted as a research agenda for the classroom, one that recognises its complexities. In this paper, we make several proposals as to how to get from laboratory findings to a classroom-based research agenda.